2023
DOI: 10.3390/ijms24032152
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD22 in Triple-Negative Breast Cancer: A Novel Prognostic Biomarker and Potential Target for CAR Therapy

Abstract: Triple-negative breast cancer (TNBC) accounts for 15–20% of all breast cancer cases. Due to the lack of expression of well-known molecular targets [estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2)], there is a need for more alternative treatment approaches in TNBC. Chimeric antigen receptor (CAR)-T cell-based immunotherapy treatment is one of the latest treatment technologies with outstanding therapeutic advances in the past decade, especially in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Another potential target CD22 in TNBC is multifunctional receptor primarily expressed on the surface of lymphocytes. Zaib et al 43 identified CD22 as an upregulated gene with high expression in TNBC, suggesting its potential as a target for CAR-T cell treatment (Table 1). 2).…”
Section: Bc Subtypesmentioning
confidence: 99%
“…Another potential target CD22 in TNBC is multifunctional receptor primarily expressed on the surface of lymphocytes. Zaib et al 43 identified CD22 as an upregulated gene with high expression in TNBC, suggesting its potential as a target for CAR-T cell treatment (Table 1). 2).…”
Section: Bc Subtypesmentioning
confidence: 99%
“…Renal cancer patients featured biomarkers such as RPL36A 40 and TACC3, 41 with associations with immune-related pathways and T cell depletion. Within the realm of BRCA patients, GNPNAT1 42 surfaced as an upregulated biomarker associated with proliferation and invasiveness, CD22 43 exhibited heightened expression, correlating with tumor size, DHCR24 44 overexpression was linked to tumor growth promotion, and BUB3 45 was upregulated and negatively correlated with various immune cell types. Furthermore, low PHF2 46 expression was identified as significantly associated with poor prognosis, while FAM83H-AS1 47 and lncRNA-ATB were observed to be overexpressed in sera, demonstrating correlations with tumor metastasis, size, and lymph node metastasis and emphasizing their prognostic rather than diagnostic value.…”
Section: Resultsmentioning
confidence: 99%
“…Tuscano et al found high expression of CD22 in lung cancer cells, but was not reproducible by Pop LM [ 20 , 21 ]. What’s more, our group has published another paper to indicate CD22 expression in breast cancer [ 22 ]. Our study found that CD22 was widely expressed in the ESCC cell membrane.…”
Section: Discussionmentioning
confidence: 99%